Effect of Perpendicular Uniaxial Anisotropy on the Annihilation Fields of Magnetic Vortices - Altbir-Drullinsky, D; Allende-Prieto, S (2013)
The magnetization reversal in several nanoscopic systems is driven by the nucleation and propagation of a vortex structure that is very sensitive to the application of a magnetic field or a spin polarized current. In particular in a dot, the vortex profile is strongly affected by anisotropy, however, its role on the core behavior has not been clarified. In the present work, we investigate the influence of a perpendicular anisotropy on the annihilation and shape of magnetic vortex cores in permalloy disks. We used both micromagnetic simulations with the OOMMF code, and the analytical rigid core model that assumes that the shape of the core does not change during the hysteresis cycle. Under both approaches, the annihilation field decreases with increasing perpendicular anisotropy for almost all the structures investigated. Also a deformation of the vortex core profile is evidenced from the micromagnetic simulations, for larger anisotropy and/or dot thickness. For every dot thickness, this change does not depend on the dot radius, but on the relative distance of the core from the center of the dot. © 2013 AIP Publishing LLC.